2017
DOI: 10.3389/fmed.2017.00196
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in the Portuguese Older Adults: Prevalence and Associated Factors

Abstract: Anxiety and depression in the elderly individuals have been studied around the world, and some authors consider them among the most serious problems faced by modern societies. With recent economic crisis—very important in Southern European countries—isolation, loneliness, and exclusion of the active society, mental problems are probably raising and associated with distinct factors. In this cross-sectional analysis, nested in a longitudinal population-based cohort study, we analyze anxiety and depression preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
2
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 45 publications
6
54
2
6
Order By: Relevance
“…The frequency of depressive symptoms in previous studies was 18.5%-56.6% in community-based investigations, in Turkey (11,12,17,18). A community-based study conducted in South Africa using the GDS found depressive symptoms in 40% of the elderly (6). In contrary, depression prevalence in the elderly population is lower (range 9.0% -11.0%) in developed countries than underdeveloped countries (19,20).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The frequency of depressive symptoms in previous studies was 18.5%-56.6% in community-based investigations, in Turkey (11,12,17,18). A community-based study conducted in South Africa using the GDS found depressive symptoms in 40% of the elderly (6). In contrary, depression prevalence in the elderly population is lower (range 9.0% -11.0%) in developed countries than underdeveloped countries (19,20).…”
Section: Discussionmentioning
confidence: 97%
“…The World Health Organization (WHO) has reported that the most common mental disorder in older adults is depression, which affects approximately 7% of the world's elderly population, and clinically significant depressive symptoms have been reported in 15% of older adults (4). Depression prevalence rates differ among countries: a recent population-based study found that 41.8% of the elderly had depressive symptoms in Ethiopia (5), 40.0% in South Africa (6) and 42.7% in India (7). Globally, clinically significant depressive symptoms exist in one in every eight elderly individuals living in the community; however, the depression rate is higher in inpatient older adults and in those who reside in nursing homes (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niektórzy badacze uważają nawet, że jest to jeden z najważniejszych problemów współczesnego społe-czeństwa (de Sousa et al, 2017).…”
Section: Aktywność Fizyczna a Lęk I Depresja Jako Wybrane Aspekty Fununclassified
“…Inne badania populacji polskiej pokazują, że ciężkie objawy depresji ujawnia 10,9% osób powyżej 65. roku życia (Kujawska-Danecka et al, 2016). Podobnie badania wykonane na populacji portugalskiej wykazały, że występowanie depresji i lęku jest powszechnym problemem osób starszych i dotyczy 9,6% populacji dla depresji i 11,8% dla lęku (de Sousa et al, 2017).…”
Section: Aktywność Fizyczna a Lęk I Depresja Jako Wybrane Aspekty Fununclassified